Nickel-lanthanum-cobalt layered perovskite and preparation method and application thereof

By activating persulfate with nickel-lanthanum cobalt layered perovskite catalyst, the problems of catalyst toxicity and metal ion leaching in the prior art are solved, efficient degradation of polyvinyl alcohol is achieved, and good stability and pH adaptability are achieved.

CN119838604APending Publication Date: 2025-04-18NANTONG UNIV +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411893788.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the prior art, when dealing with difficult-to-degrade organic pollutants such as polyvinyl alcohol, the high toxicity of catalysts and metal ion leaching problems limit their application, and the degradation efficiency is limited in complex wastewater environments.

Method used

Ni-lanthanum cobalt layered perovskite is used as a catalyst, synthesized by the sol-gel method and calcined under hydrogen to form a cobalt nanoparticle catalyst anchored on the nickel-lanthanum cobalt layered perovskite, and the persulfate is activated to degrade polyvinyl alcohol.

Benefits of technology

The catalyst exhibits high activity, significantly improved degradation efficiency, and reduces the leaching of metal ions, and has extensive pH adaptability, good stability and durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838604A_ABST
    Figure CN119838604A_ABST
Patent Text Reader

Abstract

The invention provides nickel-lanthanum-cobalt layered perovskite as well as a preparation method and application thereof, and belongs to the technical field of polyvinyl alcohol degradation. The preparation method comprises the following steps: S1, dissolving Ni (NO3) 2.6 H2O, La (NO3) 3.6 H2O and Co (NO3) 3.6 H2O in deionized water, adding ethylenediaminetetraacetic acid and citric acid, adjusting the pH value of a reaction system to 8-12, carrying out a stirring reaction, then carrying out rotary evaporation until liquid is completely evaporated, drying, and calcining in an air atmosphere to obtain a black solid; and S2, calcining the black solid in a hydrogen atmosphere to obtain the nickel-lanthanum-cobalt layered perovskite. According to the preparation method, an in-situ desolvation perovskite oxide is synthesized through a sol-gel method and then calcined under hydrogen, and the cobalt nanoparticle catalyst anchored on nickel-lanthanum-cobalt layered perovskite is synthesized through in-situ embedding and desolvation in the high-temperature phase change process, so that more active centers can be provided, and the catalytic activity of the nickel-lanthanum-cobalt layered perovskite is improved. And moreover, leaching of metal in the PMS activation process can be reduced, and the stability and durability of the catalyst can be guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyvinyl alcohol degradation and discloses a nickel-lanthanum-cobalt layered perovskite and a preparation method and application thereof. Background Art

[0002] The Fenton-like process of persulfate is an advanced oxidation technology that generates highly active free radicals by activating persulfate (PMS) or hydrogen persulfate (PDS), thereby degrading organic pollutants in water. This process has the advantages of strong oxidation ability, mild operating conditions, and no secondary pollution. It is suitable for treating organic wastewater that is difficult to degrade, such as polyvinyl alcohol wastewater.

[0003] In Fenton-like systems, the choice of catalyst is crucial. Commonly used catalysts include transition metals and their oxides, such as iron-based, manganese-based, copper-based and cobalt-based catalysts. These catalysts can activate persulfate through heterogeneous catalysis to produce sulfate radicals (SO4·-) and hydroxyl radicals (·OH), thereby effectively degrading organic pollutants. Metal redox shows high activity for PMS activation in heterogeneous catalytic reactions of cobalt-based materials, but the high toxicity and high leaching of cobalt restrict its development. It is currently expected that cobalt can be fixed on carriers such as graphene and porous polymers to solve this problem. Despite the progress made, most catalysts can only show limited performance in complex wastewater environments.

[0004] In practical applications, the activation efficiency of persulfate can be improved by optimizing the composition and structure of the catalyst, thereby improving the degradation efficiency of organic pollutants. For example, a new catalytic oxidation system with Fe-doped g-C3N4 (CNF) as PMS catalyst was constructed, which can selectively degrade phenolic organic pollutants in a wide pH range and complex water chemistry conditions.

[0005] In addition, the reaction conditions of the Fenton-like process, such as pH, temperature, pollutant concentration, and the amount of catalyst and oxidant, will affect the degradation efficiency. For example, the ZVI-Fenton system containing persulfate works best at acidic pH, but reasonable degradation effects can usually be obtained at pH values ​​close to neutral.

[0006] Therefore, it is necessary to propose a new catalyst with higher degradation efficiency, which can avoid problems such as excessive metal ion leaching and has wide adaptability to pH and can be used for the degradation of organic pollutants such as polyvinyl alcohol. Summary of the invention

[0007] In view of this, the purpose of the present invention is to provide a nickel-lanthanum-cobalt layered perovskite and its preparation method and application. The nickel-lanthanum-cobalt layered perovskite is used to activate persulfate to catalyze the degradation of polyvinyl alcohol, has the advantages of safety, high efficiency, stability, etc., shows high activity while greatly reducing the leaching of metal ions, and has a wide range of pH adaptability.

[0008] The purpose of the present invention is achieved through the following solutions:

[0009] The first aspect of the present invention provides a method for preparing nickel lanthanum cobalt layered perovskite, comprising the following steps:

[0010] S1. Dissolve Ni(NO3)2·6H2O, La(NO3)3·6H2O and Co(NO3)3·6H2O in deionized water, add ethylenediaminetetraacetic acid and citric acid, adjust the pH of the reaction system to 8-12, stir the reaction, and then rotary evaporate until the liquid is completely evaporated, dry, and calcine in air atmosphere to obtain a black solid;

[0011] S2. calcining the black solid in a hydrogen atmosphere to obtain the nickel lanthanum cobalt layered perovskite.

[0012] In some embodiments of the present invention, in step S1, the ratio of the amounts of Co(NO3)3·6H2O, Ni(NO3)2·6H2O and La(NO3)3·6H2O is 1:1:2.

[0013] In some embodiments of the present invention, in step S1, the ratio of the sum of the molar amounts of ethylenediaminetetraacetic acid and citric acid to the molar amount of La(NO3)3·6H2O is 12:1.

[0014] In some embodiments of the present invention, in step S1, the molar ratio of ethylenediaminetetraacetic acid to citric acid is (1-3):(1-3).

[0015] In some embodiments of the present invention, in step S1, adjusting the pH of the reaction system to 8-12 is specifically: adding NH3·H2O to the reaction system until the pH is 8-12.

[0016] In some embodiments of the present invention, in step S1, adjusting the pH of the reaction system is specifically adjusting the pH to 12.

[0017] In some embodiments of the present invention, in step S1, the stirring reaction time is 100-150 min.

[0018] In some embodiments of the present invention, in step S1, the calcination in air atmosphere is specifically: the calcination process is heated to 750-950°C, calcined for 4-8 hours, and the heating rate is 2-8°C / min

[0019] In some embodiments of the present invention, in step S2, the calcination in a hydrogen atmosphere is specifically: heating to 750-950° C., calcining for 4-8 hours, a heating rate of 2-8° C. / min, and a hydrogen flow rate of 30 ppm.

[0020] The second aspect of the present invention provides a nickel lanthanum cobalt layered perovskite prepared by the above-mentioned preparation method.

[0021] The third aspect of the present invention provides an application of the above-mentioned nickel lanthanum cobalt layered perovskite in degrading polyvinyl alcohol pollution.

[0022] The fourth aspect of the present invention provides a method for activating persulfate to degrade polyvinyl alcohol, which specifically comprises: adding the nickel lanthanum cobalt layered perovskite and persulfate as described in claim 8 to an aqueous solution containing polyvinyl alcohol, adjusting the pH to 3-9, and oscillating the degradation reaction until the polyvinyl alcohol is completely degraded and then stopping the reaction.

[0023] In some embodiments of the present invention, in the reaction system of the degradation reaction, the initial mass ratio of polyvinyl alcohol, nickel lanthanum cobalt layered perovskite and persulfate is (10-15):(2-18):(2-10).

[0024] In some embodiments of the present invention, in the reaction system of the degradation reaction, the initial mass ratio of polyvinyl alcohol, nickel lanthanum cobalt layered perovskite and persulfate is (10-15):6:(4-6).

[0025] In some embodiments of the present invention, the persulfate is a peroxymonosulfate with good stability and solubility.

[0026] In some embodiments of the present invention, the pH adjustment specifically includes: adjusting the pH to 5-9.

[0027] In some embodiments of the present invention, the pH adjustment is specifically: adjusting the pH to 9.

[0028] In some embodiments of the present invention, the temperature of the degradation reaction is 20-30°C.

[0029] In some embodiments of the present invention, the degradation reaction temperature is 25° C. and the reaction time is 30-120 min.

[0030] In addition, the order of addition is to add the above-mentioned nickel lanthanum cobalt layered perovskite to allow the solution to reach adsorption and desorption equilibrium, add PMS to allow the catalyst to fully contact with the oxidant, and after reacting for 60 minutes, the molecular weight after degradation can be less than 1000Da.

[0031] The nickel-lanthanum-cobalt layered perovskite and the preparation method and application thereof according to the embodiment of the present invention have at least one of the following advantages:

[0032] (1) The present invention synthesizes in-situ dissolution of perovskite oxide by a sol-gel method, and then calcines it under hydrogen. The cobalt nanoparticle catalyst anchored on the nickel-lanthanum-cobalt layered perovskite is synthesized by in-situ embedding and desolvation during the high-temperature phase change process, which can not only provide more active centers, but also reduce the leaching of metals during the PMS activation process, which helps to ensure the stability and durability of the catalyst. During this high-temperature phase change process, ordinary perovskite can be converted into layered perovskite, further enhancing electron transport and structural stability.

[0033] (2) During the high-temperature phase transition, cobalt atoms are in situ embedded and desolvated. This anchoring strategy significantly increases the Co 3+ / Co 2+ The cobalt sites around the oxygen vacancies can promote the destruction of the OH bonds of the adsorbed PMS molecules, showing excellent PMS activation ability, and can complete the degradation of polyvinyl alcohol within 60 min, which is better than most reported PMS activators.

[0034] (3) The nickel-lanthanum-cobalt layered perovskite prepared by the present invention is used to activate persulfate to degrade polyvinyl alcohol, and the Co 0 The introduction of 3+ / Co 2+ The activation rate limit of the redox system greatly improves the degradation efficiency. For the oxygen vacancy (VO) structure of the in-situ anchored desolvated perovskite, on the one hand, the metal oxide is reduced and loses oxygen. The formation of VO in the lattice makes the extra electrons in the material concentrate around the metal cations, and the valence state of the cations decreases; on the other hand, the electron-deficient VO can accept electrons from the Co 3d orbital, resulting in electron delocalization at the cobalt site, thereby promoting the adsorption of *HSO5 and *OH intermediates onto the "metal-VO bridge" structure. At the same time, Co 0 The synergistic effect of VO on the catalyst surface can destroy the OH bonds of the adsorbed PMS molecules, thereby promoting 1 The generation of O2 is beneficial to reduce the breakage barrier of the peroxide bond (-OO-) of PMS, and -OO- can be used by the more active Co 0 Destruction, generation of SO4 ·- and · OH.Co 0 Co generated after oxidation 2+ It can further participate in the subsequent oxidation reaction and generate a large number of free radicals in a short time even at low PMS concentration, thereby improving the catalytic degradation performance. 0 Can accelerate Co 3+ Towards lower valence Co2+ conversion, ensuring the continuity of the reaction and the formation of the oxidant cycle, overcoming the Co 3+ Disadvantages: Weak catalytic activity.

[0035] (4) The present invention improves the degradation efficiency of polyvinyl alcohol by persulfate by designing the dosage ratio of nickel lanthanum cobalt layered perovskite, persulfate and polyvinyl alcohol and the pH of the reaction environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] These and / or other aspects and advantages of the present invention will become apparent and readily understood from the following description of the preferred embodiments in conjunction with the accompanying drawings, in which:

[0037] Figure 1 A bar graph showing molecular weight of polyvinyl alcohol after degradation at different nickel-lanthanum-cobalt layered perovskite dosages in Example 6 of the present invention is shown;

[0038] Figure 2 A bar graph showing molecular weight of polyvinyl alcohol after degradation under different initial pH conditions in Example 7 of the present invention is shown;

[0039] Figure 3 A bar graph showing molecular weight of polyvinyl alcohol after degradation under different PMS dosage conditions in Example 8 of the present invention is shown;

[0040] Figure 4 A bar chart showing molecular weights of polyvinyl alcohol after degradation using different catalysts in Example 9 of the present invention is shown. DETAILED DESCRIPTION

[0041] The technical solution of the present invention is further specifically described below by examples and in conjunction with the accompanying drawings. In the specification, the same or similar reference numerals indicate the same or similar components. The following description of the embodiments of the present invention with reference to the accompanying drawings is intended to explain the overall inventive concept of the present invention and should not be construed as a limitation of the present invention.

[0042] In one aspect of the embodiments disclosed in the present invention, a method for preparing nickel-lanthanum-cobalt layered perovskite is provided, comprising the following steps:

[0043] S1. Dissolve Ni(NO3)2·6H2O, La(NO3)3·6H2O and Co(NO3)3·6H2O in deionized water, add ethylenediaminetetraacetic acid and citric acid, adjust the pH of the reaction system to 8-12, stir the reaction, and then evaporating the liquid until it is completely evaporated, drying, and calcining in an air atmosphere to obtain a black solid. According to the embodiment of the present disclosure, the ratio of the amount of substance of Co(NO3)3·6H2O, Ni(NO3)2·6H2O and La(NO3)3·6H2O is 1:1:2.

[0044] This step firstly synthesizes in-situ dissolution of perovskite oxide by a sol-gel method, and then calcines in an air atmosphere to improve the crystal integrity of the catalyst, increase its specific surface area and average pore size, and thus improve the catalytic performance of the catalyst.

[0045] The A / B sites of the catalyst were manipulated by alkaline regulation. La was doped at the A site of the perovskite, and Ni and Co were doped at the B site, which could achieve higher catalytic activity and remain stable after long-term operation. In addition, alkaline regulation also improved the catalyst's ability to adsorb and activate reactants. The catalytic activity was optimal at a pH of 12.

[0046] In the embodiments disclosed in the present invention, the pH of the reaction system is adjusted by adding NH 3 ·H 2 O into the reaction system.

[0047] The chemical reaction in the sol-gel process is very sensitive to pH. Ammonia, as an alkaline substance, can be used to adjust the pH value of the solution, optimize the reaction conditions, and improve the quality of the gel. An appropriate amount of ammonia can promote the formation of a uniform gel network and improve the density and stability of the material. Ammonia can act as a catalyst in the sol-gel reaction to promote the reaction process in the solution and accelerate the gelation rate. By adjusting the amount of ammonia added, the gelation process can be precisely controlled to obtain a material with an ideal structure and performance.

[0048] When preparing perovskite catalysts, the role of adding EDTA and CA is to increase the dispersion of metal ions and promote the decomposition of ligands, thereby improving the performance and stability of the catalyst.

[0049] As a ligand, EDTA can form a stable coordination compound with metal ions, thereby improving the dispersion of metal ions. Such highly dispersed metal ions help to obtain a uniform solid solution, thereby improving the performance of the catalyst.

[0050] CA is mainly used in the process of preparing perovskite catalysts by the self-combustion method. As a small molecule organic acid ligand, it can form coordination compounds with metal ions and decompose at a certain temperature to promote the uniform mixing of precursor substances and the solid-phase reaction. This method can not only improve the dispersibility of the product, but also ensure the strict control of the stoichiometric ratio, thereby obtaining high-purity perovskite materials.

[0051] In some embodiments of the present invention, in step S1, the ratio of the sum of the molar amounts of ethylenediaminetetraacetic acid and citric acid to the molar amount of La(NO3)3·6H2O is 12:1. The ratio of the molar amounts of ethylenediaminetetraacetic acid to citric acid is (1-3):(1-3).

[0052] In some embodiments of the present invention, in step S1, the calcination in air atmosphere is specifically: the calcination process is heated to 950° C., calcined for 6 hours, and the heating rate is 3° C. / min.

[0053] During the calcination process, as the temperature increases, the specific surface area and average pore size will also decrease, and the internal micropores will gradually decrease. However, the temperature cannot be too high, as too high a temperature will lead to reduced catalyst activity or even deactivation. At a temperature of 950°C, the crystal form of the perovskite catalyst becomes more perfect, and the resulting catalyst has excellent stability and catalytic activity.

[0054] S2. The black solid obtained in step S1 is calcined in a hydrogen atmosphere to obtain the nickel lanthanum cobalt layered perovskite.

[0055] Calcination under hydrogen, on the one hand, Co 0 In-situ embedding and desolvation occurred during the high-temperature phase transition, and Co 0 The in-situ generation of metal nanoparticles by exchanging and dissolving from the perovskite mother lattice to the surface can not only provide more active centers, but also reduce the leaching of metals during the PMS activation process, which helps to improve the stability of catalytic nanoparticles in the chemical cycle; on the other hand, the in-situ dissolution of perovskite oxides into a layered structure further enhances electron transport and structural stability.

[0056] Compared with the in-situ dissolution of perovskite based on traditional infiltration, cobalt atoms are in-situ embedded and desolvated during the high-temperature phase transition in hydrogen atmosphere. This unique anchoring strategy can improve the Co 3+ / Co 2+ Cycle efficiency. Co with stronger reduction activity 0 The introduction of 3+ / Co 2+ The activation rate limit of the redox system greatly improves the degradation efficiency. For the oxygen vacancy (VO) structure of the in-situ anchored desolvated perovskite, on the one hand, the metal oxide is reduced and loses oxygen. The formation of VO in the lattice makes the extra electrons in the material concentrate around the metal cations, and the valence state of the cations decreases; on the other hand, the electron-deficient VO can accept electrons from the Co 3d orbital, resulting in electron delocalization at the cobalt site, thereby promoting the adsorption of *HSO5 and *OH intermediates onto the "metal-VO bridge" structure. At the same time, Co 0 The synergistic effect of VO on the catalyst surface can destroy the OH bonds of the adsorbed PMS molecules, thereby promoting 1 The generation of O2 is beneficial to reduce the breakage barrier of the peroxide bond (-OO-) of PMS, and -OO- can be used by the more active Co 0 Destruction, generation of SO4 ·- and · OH.Co0 Co generated after oxidation 2+ It can further participate in the subsequent oxidation reaction and generate a large number of free radicals in a short time even at low PMS concentration, thereby improving the catalytic degradation performance. 0 Can accelerate Co 3+ Towards lower valence Co 2+ conversion, ensuring the continuity of the reaction and the formation of the oxidant cycle, overcoming the Co 3+ Disadvantages: Weak catalytic activity.

[0057] In some embodiments of the present invention, in step S2, the calcination in a hydrogen atmosphere is specifically: heating to 850° C., calcining for 4 hours, a heating rate of 2° C. / min, and a hydrogen flow rate of 30 ppm.

[0058] Example 1

[0059] S1.S1. Ni(NO3)2·6H2O (290.785 g, 1.0 mol), La(NO3)3·6H2O (866.02 g, 2.0 mol) and Co(NO3)3·6H2O (291.035 g, 1.0 mol) were dissolved in deionized water, ethylenediaminetetraacetic acid (1168.96 g, 4.0 mol) and citric acid (1536.96 g, 8.0 mol) were added, the pH of the reaction system was adjusted to 12, the reaction was stirred for 120 min, and then rotary evaporated until the liquid was completely evaporated, dried, placed in an air atmosphere, heated to 950°C, and calcined for 6 hours at a heating rate of 3°C / min to obtain a black solid;

[0060] S2. The black solid obtained in step S1 is placed in a hydrogen atmosphere, heated to 850°C, and calcined for 4 hours at a heating rate of 2°C / min and a hydrogen flow rate of 30 ppm to obtain nickel lanthanum cobalt layered perovskite.

[0061] Example 2

[0062] Compared with Example 1, the only difference is that the pH value of the reaction system is 10.

[0063] Example 3

[0064] Compared with Example 1, the only difference is that S2 is an air atmosphere.

[0065] Example 4

[0066] Compared with the embodiment 1, the only difference is that there is no step S2.

[0067] In other embodiments of the present invention, a method for degrading polyvinyl alcohol by activating persulfate is provided, wherein the method comprises: adding the nickel lanthanum cobalt layered perovskite prepared in Example 1 and persulfate to an aqueous solution containing polyvinyl alcohol, adjusting the pH to 3 to 9, performing a degradation reaction by oscillation until the polyvinyl alcohol is completely degraded, and then stopping the reaction. In the method, the persulfate is a peroxymonosulfate with good stability and solubility.

[0068] In some embodiments of the present invention, in the reaction system of the degradation reaction, the initial mass ratio of polyvinyl alcohol, nickel lanthanum cobalt layered perovskite and persulfate is (10-15):(2-18):(2-10).

[0069] In the reaction system of the degradation reaction, a higher catalyst (nickel lanthanum cobalt layered perovskite) addition ratio can provide more active sites and increase the contact opportunities with PMS, thereby improving the activation efficiency. However, if the addition ratio is too high, the catalyst is prone to aggregation and sedimentation, thereby reducing the total specific surface area of ​​the catalyst and the effective contact area between the catalyst and PMS, resulting in reduced catalytic efficiency. At the same time, excessive catalyst will produce a large amount of SO4 in a short period of time. ·- , these SO4 ·- It will undergo a self-quenching reaction, thereby reducing SO4 ·- The yield of 2.5% catalyzer is 1.5%, which leads to a decrease in degradation performance. Under this catalyst dosage, the whole reaction can reach a balance and achieve a good degradation efficiency.

[0070] In the reaction system of the degradation reaction, the proportion of persulfate will also affect the degradation efficiency. Too low a PMS dosage will affect the generation of singlet oxygen, while too high a PMS dosage may lead to excessive generation of free radicals, which will lead to free radical quenching reactions in the system, thereby reducing its oxidation efficiency, thereby reducing the degradation effect and increasing costs. In addition, excessive PMS will lead to reduced catalyst activity, and excessive persulfate will inhibit the activity of the catalyst and reduce the generation of effective free radicals.

[0071] In a preferred embodiment provided by the present invention, the initial mass ratio of polyvinyl alcohol, nickel lanthanum cobalt layered perovskite and persulfate is (10-15):6:(4-6).

[0072] When the degradation reaction system is acidic, a large amount of H + It will form a hydrogen bond PMS (-OO-) with the peroxide bond, inhibiting the interaction between the nickel-lanthanum-cobalt layered perovskite and PMS, thereby weakening the oxidation process. When the reaction system of the degradation reaction is alkaline, the generation rate of the active substance is promoted, thereby accelerating the degradation of the pollutants. Therefore, in some embodiments of the present invention, the pH is adjusted to 5 to 9. Preferably, the pH is adjusted to 9.

[0073] In some embodiments of the present invention, the temperature of the degradation reaction is 20-30°C.

[0074] In some embodiments of the present invention, the degradation reaction temperature is 25° C. and the reaction time is 30-120 min.

[0075] In addition, in the above method of activating persulfate to degrade polyvinyl alcohol, the order of addition is to add the above nickel lanthanum cobalt layered perovskite to allow the solution to reach adsorption and desorption equilibrium, and then add PMS to allow the catalyst to fully contact with the oxidant.

[0076] Example 6

[0077] Take 50mL of a 10g / L polyvinyl alcohol solution prepared with ultrapure water into a 100mL beaker, add a certain amount of the nickel lanthanum cobalt layered perovskite prepared in Example 1 to make its concentration 2g / L, 6g / L, 10g / L, 14g / L, 18g / L, respectively, and after the solution reaches adsorption-desorption equilibrium, add a certain amount of PMS to make its concentration in the mixed solution 2g / L. Add sodium hydroxide to make the initial pH of the solution reach 9, and react for 60 minutes. The molecular weight of polyvinyl alcohol after degradation under different nickel lanthanum cobalt layered perovskite dosages, such as Figure 1 The lower the molecular weight of the degraded polyvinyl alcohol is, the better the degradation effect is.

[0078] according to Figure 1 It can be seen that when the nickel-lanthanum-cobalt layered perovskite dosage is 6g / L, it has a better degradation effect. Increasing the catalyst dosage ratio can provide more active sites and increase the contact opportunities with PMS, thereby improving the activation efficiency. When the nickel-lanthanum-cobalt layered perovskite dosage is 6g / L, polyvinyl alcohol can be degraded within 60min. Further increasing the catalyst dosage will increase the cost and increase the risk of secondary pollution.

[0079] Example 7

[0080] Take 50mL of a 10g / L polyvinyl alcohol solution prepared with ultrapure water into a 100mL beaker, add a certain amount of the nickel-lanthanum-cobalt layered perovskite prepared in Example 1 to a concentration of 6g / L, and after the solution reaches adsorption-desorption equilibrium, add a certain amount of PMS to a concentration of 2g / L in the mixed solution. Add sodium hydroxide to make the initial pH of the solution 3, 5, 7, and 9, respectively, and react for 60 minutes. The molecular weight of polyvinyl alcohol after degradation under different initial pH conditions is as follows Figure 2 As shown, Figure 2This reflects the degradation effect of PMS activated by nickel-lanthanum-cobalt layered perovskite on polyvinyl alcohol under different pH conditions. It can be seen that in this embodiment, the degradation rate of polyvinyl alcohol increases with the increase of the pH value of the initial solution, and the degradation rate is the highest when the pH is 9. This is because the generation ratio of hydroxyl radicals increases under the condition of pH 9, which helps to improve the degradation efficiency of PVA.

[0081] Example 8

[0082] Take 50mL of a 10g / L polyvinyl alcohol solution prepared with ultrapure water into a 100mL beaker, add a certain amount of the nickel lanthanum cobalt layered perovskite prepared in Example 1 to make its concentration 6g / L, and after the solution reaches adsorption and desorption equilibrium, add a certain amount of PMS to make its concentration in the mixed solution 2g / L, 4g / L, 6g / L, 8g / L, and 10g / L, respectively. Add sodium hydroxide to make the initial pH of the solution reach 9, and react for 60 minutes. The molecular weight of polyvinyl alcohol after degradation under different nickel lanthanum cobalt layered perovskite dosages, such as Figure 3 The lower the molecular weight of the degraded polyvinyl alcohol, the better the degradation effect. The molecular weight of polyvinyl alcohol after degradation under different PMS dosage conditions is shown in Figure 3 As shown, Figure 3 The results show that the degradation of polyvinyl alcohol by PMS activated by nickel-lanthanum-cobalt layered perovskite under different PMS dosage conditions is better than that of PMS activated by nickel-lanthanum-cobalt layered perovskite under different PMS dosage conditions. It can be seen that in the reaction system, when the PMS dosage is 4g / L or 6g / L, the degradation effect is better, especially when the PMS dosage is 4g / L, the degradation effect is the best.

[0083] Example 9

[0084] Take 50mL of a polyvinyl alcohol solution prepared with ultrapure water at a concentration of 10g / L into a 100mL beaker, add a certain amount of the nickel lanthanum cobalt layered perovskite prepared in Examples 1-4 to make the concentrations 6g / L respectively, and after the solution reaches adsorption-desorption equilibrium, add a certain amount of PMS to make the concentration in the mixed solution 2g / L. Add sodium hydroxide to make the initial pH of the solution reach 9, and react for 60min. The molecular weight of polyvinyl alcohol after degradation under the dosage of the nickel lanthanum cobalt layered perovskite prepared in Examples 1-4 is as follows: Figure 4 As shown, it can be seen that the degradation effect of the nickel-lanthanum-cobalt layered perovskite prepared in Example 1 is the best.

[0085] The nickel-lanthanum-cobalt layered perovskite and the preparation method and application thereof according to the embodiment of the present invention have at least one of the following advantages:

[0086] (1) The present invention synthesizes in-situ dissolution of perovskite oxide by a sol-gel method, and then calcines it under hydrogen. The cobalt nanoparticle catalyst anchored on the nickel-lanthanum-cobalt layered perovskite is synthesized by in-situ embedding and desolvation during the high-temperature phase change process, which can not only provide more active centers, but also reduce the leaching of metals during the PMS activation process, which helps to ensure the stability and durability of the catalyst. During this high-temperature phase change process, ordinary perovskite can be converted into layered perovskite, further enhancing electron transport and structural stability.

[0087] (2) During the high-temperature phase transition, cobalt atoms were in situ embedded and desolvated to synthesize cobalt nanoparticle catalysts anchored on nickel-lanthanum-cobalt layered perovskite. This anchoring strategy significantly increased the Co 3+ / Co 2+ The cobalt sites around the oxygen vacancies can promote the destruction of the OH bonds of the adsorbed PMS molecules, showing excellent PMS activation ability, and can complete the degradation of polyvinyl alcohol within 60 min, which is better than most reported PMS activators.

[0088] (3) The nickel-lanthanum-cobalt layered perovskite prepared by the present invention is used to activate persulfate to degrade polyvinyl alcohol, and the Co 0 The introduction of 3+ / Co 2+ The activation rate limit of the redox system greatly improves the degradation efficiency. For the oxygen vacancy (VO) structure of the in-situ anchored desolvated perovskite, on the one hand, the metal oxide is reduced and loses oxygen. The formation of VO in the lattice makes the extra electrons in the material concentrate around the metal cations, and the valence state of the cations decreases; on the other hand, the electron-deficient VO can accept electrons from the Co 3d orbital, resulting in electron delocalization at the cobalt site, thereby promoting the adsorption of *HSO5 and *OH intermediates onto the "metal-VO bridge" structure. At the same time, Co 0 The synergistic effect of VO on the catalyst surface can destroy the OH bonds of the adsorbed PMS molecules, thereby promoting 1 The generation of O2 is beneficial to reduce the breakage barrier of the peroxide bond (-OO-) of PMS, and -OO- can be used by the more active Co 0 Destruction, generation of SO4 ·- and · OH.Co 0 Co generated after oxidation 2+ It can further participate in the subsequent oxidation reaction and generate a large number of free radicals in a short time even at low PMS concentration, thereby improving the catalytic degradation performance. 0 Can accelerate Co 3+ Towards lower valence Co 2+ conversion, ensuring the continuity of the reaction and the formation of the oxidant cycle, overcoming the Co3+ Disadvantages: Weak catalytic activity.

[0089] (4) The present invention improves the degradation efficiency of polyvinyl alcohol by persulfate by designing the dosage ratio of nickel lanthanum cobalt layered perovskite, persulfate and polyvinyl alcohol and the pH of the reaction environment.

[0090] Although the present invention has been disclosed above through the best embodiment, it is not intended to limit the present invention. Any person skilled in the art may make some modifications and improvements without departing from the spirit and scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the definition of the claims.

Claims

1. A method for preparing nickel-lanthanum-cobalt layered perovskite, characterized in that: The following steps are involved: S1. Dissolve Ni(NO3)2·6H2O, La(NO3)3·6H2O and Co(NO3)3·6H2O in deionized water, add ethylenediaminetetraacetic acid and citric acid, adjust the pH of the reaction system to 8-12, stir the reaction, and then rotary evaporate until the liquid is completely evaporated, dry, and calcine in air atmosphere to obtain a black solid; S2. calcining the black solid in a hydrogen atmosphere to obtain the nickel lanthanum cobalt layered perovskite.

2. The preparation method according to claim 1, characterized in that: In step S1, the ratio of the amounts of Co(NO3)3·6H2O, Ni(NO3)2·6H2O and La(NO3)3·6H2O is 1:1:

2.

3. The preparation method according to claim 2, characterized in that: In step S1, the ratio of the sum of the molar amounts of ethylenediaminetetraacetic acid and citric acid to the molar amount of La(NO3)3·6H2O is 12:

1.

4. The preparation method according to claim 3, characterized in that: In step S1, the molar ratio of ethylenediaminetetraacetic acid to citric acid is (1-3):(1-3).

5. The preparation method according to claim 1, characterized in that: In step S1, adjusting the pH of the reaction system to 8-12 is specifically: adding NH3·H2O to the reaction system until the pH is 8-12.

6. The preparation method according to claim 1, characterized in that: In step S1, the stirring reaction time is 100-150 minutes.

7. The preparation method according to claim 1, characterized in that: In step S1, the calcination in air atmosphere is specifically: heating to 750-950° C., calcining for 4-8 hours, and a heating rate of 2-8° C. / min.

8. The preparation method according to claim 1, characterized in that: In step S2, the calcination in a hydrogen atmosphere is specifically as follows: after heating to 750-950°C, calcining for 4-8 hours, a heating rate of 2-8°C / min, and a hydrogen flow rate of 30ppm.

9. A nickel-lanthanum-cobalt layered perovskite prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the nickel-lanthanum-cobalt layered perovskite according to claim 9 in degrading polyvinyl alcohol pollution.